Pengaruh Pengetahuan, Kualitas Pelayanan, Produk, dan Religiusitas terhadap Minat Nasabah untuk Menggunakan Produk Simpanan pada Lembaga Keuangan Mikro Syariah - Abdul Haris Romdhoni; Dita Ratna sari (Jurnal Ilmiah Ekonomi Islam, 2018)
This study aims to examine the influence of knowledge, service quality, product, and religiosity on customers' interest in using savings products at BMT Amanah Ummah Gumpang Kartasura, Sukoharjo. In this study for independent variables are knowledge, service quality, product, and religiosity, while for the dependent variable in this study is the interest of customers using deposit products. This study uses a sample of 100 people with sampling using a random sampling method. This study uses quantitative methods and primary data using a questionnaire that must be answered by the respondent. Data analysis in this study used Multiple Linear Regression. The results of this study can be concluded based on the t test, the variables of knowledge and religiosity have an influence on the interest of customers using savings products. While service and product quality variables do not have an influence on customer interest by using deposit products. Based on the F test shows that the knowledge, quality of service, products, and religiosity simultaneously influence the interest of customers to use savings products at BMT Amanah Ummah Gumpang Kartasura, Sukoharjo.